STUDENT CENTERED LEARNING DALAM SURAH AL-KAHFI - Fitriyah, Lailatul (TA'LIMUNA: Jurnal Pendidikan Islam, 2020)
Surah Al-Kahf is a Surah that consist of three main stories, namely the story of ashab al-kahfi, the story of the owner of the date-palm garden and his companions and the sotry of the scientific journey of the Prophet Musa and the Prophet Khidir. maudhuâ€™Imethod was used in this research. In surah Al-kahfi applied the SCL (Student Centered Learning)approach, both in terms of learning methods and the characteristics of SCL. The result of this research could be concluded as follows: 1) There are some students Centered Learning in Surah Al-Kahfi. Those are: a) As a story method. It means that in this method, Allah as the wisest educator wants that human beingÂ  can take ibrah from the story mentioned in this Surah. In this case the story of ashab al-kahfi, the story of the owner of the date-palm garden and his companions and the sotry of the scientific journey of the Prophet Musa and the Prophet Khidir. b)as a ways to discuss c) as a study case method, d) as asking-questioning method, e) as a ways of giving some excercises. 2) there is also some criteria of Student Centered Learning, namely: a) there is a high motovation in learning process, b) there are two best educators in surah Al-Kahf; Allah and Prophet Khidir, c) it raises the autonomous learning, d) there is a high motivation e) and the last, it rases a responsibility.